FAKTOR FUNDAMENTAL YANG MEMPENGARUHI PERUBAHAN HARGA SAHAM (Studi Empiris pada Perusahaan Finansial yang Terdaftar Di BEI Tahun 2009dan 2010) - Norita Citra Yuliarti (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
This study aims to examine the fundamental factors of Current Ratio (CR), Leverage Ratio, Net Profit Margin (NPM), Total Assets Turn Over (TATO), Earnings Per Share(EPS)effect on stock price changes on financial companies in Indonesia . The share price is the value of a stock that reflects the wealth of the company issuing the shares, which change or fluctuation is largely determined by the forces of supply and demand occurred in the stock exchange (secondary market). The influence of these factors on stock prices is tested with regression analysis. Study sample is 40 companies listed on the Indonesian stock exchange are selected by purposive sampling.The results of this study indicate that the partial net profit margin of only variable that significantly influence the stock price, while the variable current ratio, leverage ratio, total assets turnover and earnings per shareno significant effect on stock prices. While simultaneously variable Current Ratio (CR), Leverage Ratio, Net Profit Margin (NPM), Total Assets Turn Over (TATO), Earnings Per Share(EPS)significantly influence the stock price. These results indicate that investors in making investment decisions take into consideration the level of stock prices, returns that would be obtained and also consider the ability of illiquid instruments (funds from third parties, received a loan of more than three months, and core capital) against liabilities (current debt ) company. Keywords: Stock Price, Current Ratio(CR), LeverageRatio, Net ProfitMargin(NPM), TotalAssetsTurn Over(TATO), Earnings Per Share(EPS)